Desempenho zootécnico e expressão gênica em camarões Penaeus vannamei alimentados com rações suplementadas com as microalgas Arthrospira platensis, Chlorella vulgaris e Conticribra weissflogii - Maia, Hudson Damasceno (2024)
It is very important to seek ways to increase the immunological response of shrimp in culture to allow the sustainable growth of this economic activity. The use of immunostimulating compounds appears as an alternative to promote a greater state of immunocompetence and animal well-being. The present work sought to evaluate the growth performance and immunerelated genes expression in Penaeus vannamei shrimp fed with feed supplemented with 0.5% of the microalgae Arthrospira platensis, Chlorella vulgaris and Conticribra weissflogii. A total of 768 shrimp weighing 0.43 ± 0.02 g (0.40 – 0.48 g) were transferred to 16 circular polyethylene tanks with a useful volume of 0.5 m³ under 48 shrimp tank-1 . The animals were fed experimental diets for 43 days. At the end of the experimental period, the animals were collected, counted and weighed to calculate survival and growth performance (final body weight, apparent feed consumption, final productivity and feed conversion ratio) in the respective treatments. Five animals from each tank were sampled after five days of cultivation and at the end of the experiment for gene expression analyzes from the hepatopancreas. Supplementing the experimental diets with the microalgae A. platensis, C. vulgaris and C. weissflogii had a notable positive impact on the survival rate, final productivity and feed conversion ratio. However, there was no significant improvement in the parameters final body weight and apparent feed intake. The supplementation stimulus only significantly affected the expression of two genes, TGF and TNF, which were expressed at high levels only in shrimp fed with A. platensis after 42 days of cultivation, microalgae, which improved the immunocompetence status of the animals. New studies are needed to offer new perspectives on investigating the molecular processes that drives the immune system and metabolic reactions in shrimp.